A rational approach to manage surgical procedures in COVID Era - A perspective based on experience in a private referral hospital - Rama Gupta; Bishav Mohan; Kamakshi Garg; Ashima Taneja; Satpal S Virk; Anju Grewal; Rajesh Mahajan (Wolters Kluwer Medknow Publications, 2020)
Background and Aims: COVID-19 disease has imposed challenges in caring for non-Covid elective surgical patients. As elective surgeries become essential, we propose to evaluate our approach and outcomes of surgical procedures performed during the initial period of COVID-19 pandemic so as to provide a road-map for safer approach. Material and Methods: We retrospectively evaluated outcomes in patients who underwent essential elective and emergency surgeries during the 5-week period between April 18, 2020 and May 28, 2020. All patients were screened at the front desk on their arrival to identify possible exposure to SARS- CoV-2. Nasopharyngeal swab of patients requiring hospital admission was tested for COVID-19 by quantitative RT-PCR. Patients needing essential elective surgery were taken up for surgery if they tested negative for COVID-19. Emergency procedures were undertaken in a demarcated theatre for COVID after taking level-3 protection without delay. The clinical data was reviewed and analysed. Results: A total of 764 surgical procedures were conducted, of which 70.7% were elective essential surgeries, with 95.4% of these patients being discharged in stable healthy condition. Approximately 23% of the elective and 26% of the emergency surgeries was categorised in the surgical difficulty category III and majority of these were performed under general anesthesia. Postoperative mortality was 1.04%, but the overall mortality rate was approximately 2.5%. Only two patients (0.3%) tested positive for COVID-19 in our series. Conclusion: A robust preoperative screening and testing can enable safe scheduling of essential elective surgeries.